THE ROLE OF PHYSICAL EDUCATION IN SUPPORTING STUDENT DISCIPLINE IN ELEMENTARY SCHOOLS - Yuli Santoso; Burhan Eko Purwanto; Suriswo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Physical Education has strategic potential in shaping elementary school students' discipline due to its activity-based learning characteristics, rules, and direct experience. This study aims to analyze the role of Physical Education in shaping elementary school students' discipline through the learning process that takes place in the school environment. The study used a qualitative approach with a descriptive design. The research subjects included Physical Education teachers and elementary school students. Data were collected through semi-structured interviews, learning observations, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions by applying triangulation of sources and techniques to ensure data validity. The results of the study indicate that the formation of student discipline through Physical Education takes place through teacher role models, the application of clear and consistent learning rules, and the habituation of disciplined behavior integrated into physical activities. Students learn to understand the meaning of discipline through direct experience that links orderly behavior with the smooth running of learning activities. This study concludes that Physical Education not only functions as a means of developing physical abilities, but also as an effective vehicle for internalizing the value of discipline in the learning lives of elementary school students.